Restorasi Budi Pekerti Perspektif PAI sebagai Solusi Menghadapi Krisis Moral di Era Global - Fathimatuzzahro Fathimatuzzahro; Alifia Dwi Azzahra; Akbar Izham Bayhaqi; Moh. Faizin (ALSYS, 2026)
Although moral character restoration has received broad attention in previous studies, research that specifically discusses strategies for integrating the concept of Tazkiyatu An-Nafs and the value of Ihsan into the contemporary Islamic Religious Education (PAI) curriculum remains limited. This study aims to analyze the implementation of PAI-based moral character restoration as an alternative solution to addressing the moral crisis among young people in the global era. This study used a qualitative approach with a library research design through the analysis of various relevant primary and secondary literature. Data were collected using an in-depth literature text review method and analyzed using the content analysis technique of the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The findings showed that the reconstruction of Al-Ghazali’s ethical thought through habituation, exemplary conduct, and the internalization of Ihsan-based spiritual-moral awareness can serve as an independent filter for adolescents in protecting themselves from the negative impacts of globalization. The conclusion of this study affirms the importance of integrating the values of Tazkiyatu An-Nafs and Ihsan into PAI learning as a foundation for moral character restoration oriented toward the formation of noble character. The implications of this study emphasize the need for synergy within the Three Centers of Education ecosystem to realize sustainable moral restoration for young people.